2005
DOI: 10.1590/s0100-83582005000300006
|View full text |Cite
|
Sign up to set email alerts
|

Correlação da distribuição espacial do banco de sementes de plantas daninhas com a fertilidade dos solos

Abstract: RESUMO -O objetivo deste trabalho foi identificar correlações entre o banco de sementes das plantas daninhas e os atributos da fertilidade dos solos. As amostragens de solo para determinação do banco de sementes foram feitas simultaneamente à amostragem para a análise da fertilidade do solo, utilizando uma grade amostral regular de 20 x 20 m. Os mapas de infestação e de atributos de fertilidade dos solos foram gerados pela técnica de interpolação por "krigagem". Os valores de correlação entre o banco de sement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 7 publications
(3 reference statements)
2
12
1
2
Order By: Relevance
“…Higher weed coverage and density on P rich soils have also been reported by Iwara et al (2011). Although significant correlation between C. rotundus density and high P contents has been reported by Shiratsuchi et al (2005); there was higher affinity for K contents than P contents in the present study.…”
supporting
confidence: 68%
“…Higher weed coverage and density on P rich soils have also been reported by Iwara et al (2011). Although significant correlation between C. rotundus density and high P contents has been reported by Shiratsuchi et al (2005); there was higher affinity for K contents than P contents in the present study.…”
supporting
confidence: 68%
“…However, in Brazil, little is known about the spatial variability of weeds. The first works were Shiratsuchi et al (2004Shiratsuchi et al ( , 2005, Schaffrath et al (2007) and Monquero et al (2008) whose studied the spatial distribution of weed in order to determine specific zones of management. Other studies emphasized the importance of studying the weeds distribution and specific management sites.…”
Section: Introductionmentioning
confidence: 99%
“…Bressan et al (2006) used geostatistics techniques to classify the risk of weed infestation, and made the decision on the best management for each field area. Shiratsuchi et al (2005) also reported that most studies that focused on weeds mapping had as a primary concern mapping the emerging flora during the critical cycle of interference, being the only few studies on spatial variability of weeds in the course of the crop cycle. Allied to this, studies focusing on weed parameters analysis of species diversities of the communities try to determine the degree of infestation, being one of the first steps in studying the weeds dynamics and the choice of strategies control (Lacerda et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the three species showed spatial stability between years (September 07/May 2008). The results of patch persistence over time vary between species depending on their bioecological characteristics, but need to be combined with weed management practices in the field, such as herbicide application and direction of machine work at cultivation and harvesting or soil fertility (Shiratsuchi et al, 2005).…”
Section: Resultsmentioning
confidence: 99%